Antioxidant and renoprotective effects of Spirogyra neglecta (Hassall) Kützing extract in experimental type 2 diabetic rats - Ontawong A. (2014)
Spirogyra neglecta extract (SNE) has shown antihyperglycemia and antihyperlipidemia in type 2 diabetic mellitus (T2DM) rats. This study investigated the antioxidant and renoprotective effects of SNE in T2DM rats induced by high-fat diet with low-single dose streptozotocin. T2DM rats were fed daily with SNE (0.25, 0.5, and 1 g/kg BW) for 12 weeks. Renal morphology, malondialdehyde levels, qPCR, and western blotting were analyzed. Renal cortical slices were used to determine renal transport of organic anions, which are estrone sulfate and para-aminohippurate, mediated through organic anion transporter 3-Oat3. Insulin and PKC ζ were known to activate Oat3 function while it was inhibited by PKC α. Compared to T2DM, plasma glucose, triglyceride, insulin resistance, renal morphology, and malondialdehyde levels were significantly improved by SNE supplementation. Reduced glutathione peroxidase and nuclear factor B expressions were related to antioxidant effect of SNE. Oat3 mRNA and protein were not different among groups, but insulin-stimulated rOat3 followed by anion uptakes was abolished in T2DM. This was restored in the slices from SNE treatment. The mechanism of SNE-improved Oat3 was associated with PKC α and PKC ζ expressions and activities. These findings indicate that SNE has beneficial effects on renal transport through antioxidant enzymes and PKCs in T2DM rats. © 2013 Atcharaporn Ontawong et al.